Solar-driven ionic power generation via a film of nanocellulose @ conductive metal–organic framework. Issue 2 (22nd January 2021) - Zhou, Shengyang; Qiu, Zhen; Strømme, Maria; Xu, Chao
Abstract : The new technology of "solar-driven ionic power generation" based on ionic thermophoresis and electrokinetic effects could convert solar energy into electricity by using a film of nanocellulose @ conductive metal–organic framework. Abstract : Solar energy fits well with the increasing demand for clean sustainable energy. This paper describes a freestanding hybrid film composed of a conductive metal–organic framework layered on cellulose nanofibres which enables efficient solar power generation. The working principle, which is different from the mechanisms of traditional photovoltaic or solid-state thermoelectric generation systems, is based on ionic thermophoresis and electrokinetic effects. Given the strong light absorption and low thermal conductivity of the film, a large thermal gradient can be produced on the surface under light illumination to induce fast water evaporation in an aqueous electrolyte. The thermal gradient and the water evaporation drive selective ion transport through the charged nanochannels, which generates ionic thermoelectric and streaming potentials, respectively. The assembled device can produce a sustained voltage output of ∼1.1 V, with a high power density of up to 15 W m −2 under one sun illumination. This study provides a new route for solar power generation.